The Translation of English Notice into Indonesian Language - Akhmad Baihaqi; Neni Oktaviani (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2019)
This study is discussing about the types of English imperative used in notices, the way of constructing English imperative and Indonesian imperative, and the reason of translation procedure are being applied. A Qualitative method is applied to answer the research problems. Data of the research were taken from some notices as the SL that found around Cahaya Madani Banten Boarding School along with their translation into Indonesian text (TL) used as the data source. The result shows that there are three types of imperative sentence of English imperative sentence in notices found in SMAN CMBBS translated from English into Indonesian: negative command, request, and positive command. Seeing from the process of imperative constructions of the SL, it can obviously be stated that it is formed by syntactical process, whereas in TL it is formed by morphological process that is by attaching the marker. The result also shows that there are four types of translation procedure used in this study. All of them are oriented towards the target language. Those procedures are: borrowing, modulation, transposition, and literal translation.